Characterization of Aerosol Aging Potentials at Suburban Sites in Northern and Southern China Utilizing a Potential Aerosol Mass (Go:PAM) Reactor and an Aerosol Mass Spectrometer. Issue 10 (29th May 2019) - Li, Jinjian; Liu, Qianyun; Li, Yongjie; Liu, Tengyu; Huang, Dandan; Zheng, Jing; Zhu, Wenfei; Hu, Min; Wu, Yusheng; Lou, Shengrong; Hallquist, Åsa M.; Hallquist, Mattias; et al.
Abstract: Aerosol mass spectrometry was used to characterize submicron aerosols before and after aging in a Gothenburg Potential Aerosol Mass (Go:PAM) reactor at two suburban sites in China, one in northern China at Changping (CP), Beijing, and a second in southern China at Hong Kong (HK). Organic aerosol (OA) dominated in the ambient nonrefractory particulate matter <1 μm (NR‐PM1 ) for both CP (42–71%) and HK (43–61%), with a large contribution from secondary OA factors that were semivolatile oxygenated (SVOOA) and low‐volatility oxygenated (LVOOA). Under constant OH exposure, OA enhancement (78–98%) dominated the NR‐PM1 mass increment at both sites, while nitrate was enhanced the most among the inorganic species (7–9%). Overall, the CP site exhibited higher OA oxidation potential and more enhancement of SVOOA than LVOOA (7.5 vs. 2.7 μg/m 3 ), but the reverse was observed in HK (0.8 vs. 2.6 μg/m 3 ). In CP, more enhancement of the less oxygenated SVOOA suggests that aerosol aging was more sensitive to the abundant locally emitted primary OA and volatile organic compound precursors. On the contrary, the more formation of the highly oxidized LVOOA in HK indicates that aerosol aging mainly escalated the degree of oxygenation of OA as ambient aerosol was already quite aged and there was a lack of volatile organic compound precursors. The comparative measurements using the same oxidation system reveal distinct key factors and mechanisms that influence secondary aerosol formation in two suburban locations in China, providing scientific insights to assist formulation of location‐specific mitigation measures of secondary pollution. Plain Language Summary: Atmospheric submicron particles have significant impacts on the climate and human health. A large part of these particles are formed secondarily through successive aging of primary emissions. To study such aging processes, we used a reactor that can provide highly oxidizing conditions to simulate the oxidation of ambient aerosols at accelerated rates. An online mass spectrometer was connected after the reactor to measure changes in aerosol mass concentration and chemical composition between the ambient samples and the oxidized ones. We presented the first comparative measurements of the aging potentials of ambient aerosols in two suburban sites in northern and southern China (Changping District in Beijing, and Hong Kong). Results showed that generally aerosols at the Changping site had higher aging potentials after passing through the oxidation reactor, probably due to more local emissions of precursors, while air masses in Hong Kong were already in a higher oxidation state with lower aging potentials, mainly because of strong impacts from long‐range transported pollution sources. Distinct aerosol aging pathways related to different ambient precursors were observed at the two sites. Understanding of the different characteristics of aerosol aging processes can lead to advances in air quality modeling and pollution management. Key Points: Aging processes of submicron nonrefractory aerosols were investigated comparatively at two suburban sites in northern and southern China Both sites showed dominant mass increment from organics after aging, but aerosols in northern China had higher aging potential The distinct aging processes at the two sites reflected influence from ambient precursors